Effect of Cryopreserved Cord Blood on Activity of Alveolar Macrophages in Experimental Model of Influenza - Kozhina, Olga Yu.; Ostankov, Maksim V.; Ostankova, Lyudmila V.; Bondarovich, Nikolay A.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2013)
Formation of resistance to influenza virus of type A in mice following introduction of cryopreserved human cord blood leucoconcentrate (cHCBL) or its components (plasma, nucleated cells). Bronchoalveolar lavage was obtained from mucous membrane of respiratory tract in experimental animals during influenza development. Analyzis of cell composition of bronchoalveolar lavage as well as functional activity of alveolar macrophages in lungs of animals in 7 and 14 days following influenza virus introduction. The infectioning was performed in 6 month after preventive intranasal introduction of cHCBL or its components. It was found that cHCBL in more extent than its components corrected the functional activity of alveolar macrophages increasing their phagocytic activity and preventing the immune deficiency development in animals with inducted viral pathology. Probl Cryobiol Cryomed 2013; 23(3):247–259.